106k views
4 votes
Simplify: 3x – 5 + 23x – 9

a. 2(14x -6)
b. 3x(13x-6)
c. 2(13x -7)
d. 3x(13x - 5)

2 Answers

5 votes

Answer :

C

Explanation:

  • (a+b)(a-b) = a² - b²
  • a( b + c) = ab + ac
  • a (b - c) = ab - ac
  • a( b + c) + d( b + c) = (a + d) (b + c)

3x – 5 + 23x – 9 = 26x - 14

2 . 13x = 26x

2. -7 = -14

2 ( 13x -7) so answer is C

or another way :

a. 2(14x -6) = 28x - 12

b. 3x(13x-6) = 39x² - 18x

c. 2(13x -7) = 26x - 14

d. 3x(13x - 5) = 39x² -15x

so answer is C

Hope this helps ^-^

User Eddwhis
by
5.3k points
0 votes

Explanation:

3x-5+23x-9

26x-5-9=26x-14

2(13x-7)

User Karias Bolster
by
5.0k points